Performance evaluation of integrated adsorption-nanofiltration system for emerging compounds removal: Exemplified by caffeine, diclofenac and octylphenol. (1st February 2019) - Huang, Zhujian; Gong, Beini; Huang, Chin-Pao; Pan, Shu-Yuan; Wu, Pingxiao; Dang, Zhi; Chiang, Pen-Chi
Abstract: Emerging pollutants introduced into surface water pose potential hazards to the safety of drinking water. In this study, the removal performance of three emerging compounds (exemplified by caffeine, diclofenac and octylphenol, with different physico-chemical properties) from synthetic water and source water by combining activated carbon (AC) adsorption and nanofiltration (NF) membrane processes was evaluated and analyzed. Results from synthetic water showed that the adsorption isotherms modeled well with the Langmuir equation. The removal performance of target compounds by AC-NF system was more remarkable than that of NF-AC combination. In the source water system, the integrated AC-NF process with coagulation pretreatment (the alum dosage of 60 mg/L) achieved satisfactory performance (the removal efficiencies of three target compounds reached > 95%). Results showed the electrostatic interaction and pollutant hydrophobicity determined the behavior and the fate of selected PPCPs/EDCs during the sequential treatment process of coagulation, activated carbon adsorption, and NF membrane separation. Finally, the AC and NF membranes were analyzed by Fourier transform infrared spectroscopy and scanning electron microscopy to understand the mechanisms, i.e. electrostatic and hydrophobic effects on the total removal process. It suggests that the integrated AC-NF process with coagulation pretreatment should be a feasible approach for removing emerging compounds in waterworks. Graphical abstract: Image 1 Highlights: The removal of PPCPs/EDC by coagulation is mainly caused by fine floc adsorption. The removal rate of PPCPs/EDC and DOC by coagulation-AC-NF process achieved >95%. The removal rate and mechanism of PPCPs/EDC by each processing unit were proposed. The behavior of PPCPs/EDC in coagulation-AC-NF system could be better understood.